Acute hepatitis B virus infection in pregnancy: a case report of three patients with comorbid anxiety and their clinical outcomes - Wu, Shenlu; Hu, Kejie; Wang, Yufang (Frontiers in Psychiatry, 2025)
This case series reports three pregnant women with acute hepatitis B virus (AHB) infection, exploring their clinical outcomes and comorbid anxiety. All three patients presented with abnormal liver function and positive HBV markers. They received supportive therapy (liver-protective, enzyme-lowering agents, etc.), achieving HBsAg clearance and virological cure, with normal liver function during follow-up (one patient lost to follow-up). Despite favorable biomedical outcomes, all experienced significant anxiety over maternal-fetal health and disease progression. This study emphasizes that AHB in pregnancy, though usually self-limited, requires integrating psychosocial support into multidisciplinary management to address perinatal mental health, supporting WHO’s 2030 viral hepatitis elimination goal.